Response surface methodology optimization of enzymatic hydrolysis of Lentinus edodes and analysis of product ingredients functions - Zheng, Bowei; Wu, Xiaoqi; Qiao, Tonglei; Ding, Qiang; Wang, Honglei (Frontiers in Sustainable Food Systems, 2025)
The increasing demand for natural flavor enhancers and functional food ingredients has driven interest in Lentinus edodes (shiitake mushrooms), which are rich in proteins and bioactive compounds. This study optimized the enzymatic hydrolysis of L. edodes using various proteases and response surface methodology. Single-factor experiments were conducted, and flavor protease was identified as the most effective enzyme. The optimal hydrolysis conditions were 50.268°C, 5.23% material ratio, and 223.64 kU/100 g protease dosage, with a predicted amino acid nitrogen raise ratio of 268.908%. Validation tests gave an average of 267.6 ± 0.7%, with <5% deviation. After hydrolysis, glutamic acid, aspartic acid, and alanine increased, enhancing umami and sweetness. Essential amino acids such as lysine, valine, and isoleucine also rose significantly. Antioxidant activity was confirmed by DPPH and ·O₂- scavenging, with IC₅₀ values of 2.536 and 2.013, respectively. These results demonstrate that enzymatic hydrolysis is a promising approach to improve both the taste and nutritional value of L. edodes, supporting its application in natural seasoning and functional food development.